PENGARUH PENGKONDISIAN TERHADAP KINERJA CAMPURAN BERASPAL PANAS DAUR ULANG DENGAN KADAR RAP TINGGI - Dani Hamdani; Nono - (Direktorat Bina Teknik Jalan dan Jembatan, 2020)
The hot mix asphalt recycling design and construction will be successful if it is proven by the good performance of the asphalt mixture in the laboratory and in the field. The performance hot mix asphalt recycling (ACWCRAP) tested was Marshall properties, deformation resistance, and fatigue resistance. The test objects used are those that have been conditioned in a heating oven and standar speciment according to the AASHTO R30-02 procedure. The purpose of this study was to examine the effect of conditioning on the performance of the hot mix asphalt recycling with high RAP. High RAP is the use of RAP material in a hot mix asphalt recycling with 3 variations of the used RAP material (60%, 80% and 100%). The conclusion of this experiment is that all the properties of the asphalt mixture meet the requirements. The ACWCPolymer stability value is equivalent to ACWC with 100% RAP, but for the stability value with the conditioned specimen (STOA), the ACWC with 100% RAP stability is higher. The stability of ACWC with 60% RAP and 80% RAP is lower than the stability of ACWCPolymer. Stability the ACWCPolymer with STOA test specimen is equivalent to ACWC with 80% RAP, while for ACWC with 60% RAP it is still lower than the stability of ACWCPolymer. All dynamic stability hot mix asphalt recycling has meet requirements. With the use of higher RAP, ACWCRAP is more resistant to deformation, both for fresh and STOA specimens. ACWC with 100% RAP is higher than ACWCPolymer deformation resistance, but for STOA specimens, the deformation resistance of ACWCPolymer is higher than other asphalt blends. Based on these facts, the deformation resistance performance of ACWCPolymer is better than ACWCRAP. With the tensile strain reference of the asphalt mixture permit of 100 ÂµÉ›, the ACWCRAP mixture, both fresh and STOA specimens, is more fatigue resistant than ACWCPolymer. Comparing between the three ACWCRAP that used 100% RAP was the most fatigue resistant.